2010
DOI: 10.1160/th09-12-0815
|View full text |Cite
|
Sign up to set email alerts
|

The EP3-agonist sulprostone, but not prosta glandin E2 potentiates platelet aggregation in human blood

Abstract: Dear Sirs, Acute coronary syndromes, myocardial infarction and ischaemic stroke are leading causes of mortality and morbidity. Atherosclerosis, the basis for these diseases, has an important inflammatory component, and macrophages accumulating in atherosclerotic arteries produce prostaglandin E 2 (PGE 2), a major inflammatory mediator (1-3). Recently, it has been reported in mice that PGE 2 accumulating in inflammatory atherosclerotic lesions might contribute to atherothrombosis after plaque rupture (4). Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…1). We and others reported previously that sulprostone, a selective EP 3 -agonist, does not activate platelets on its own, but shows a potentiation of platelet aggregation induced by various agonists, such as U46619, collagen and ADP [18,[24][25][26]. We found that both EP 3 -antagonists showed a concentration-dependent inhibitory effect of the sulprostone-dependent potentiation of U46619-induced aggregation, which was significant for all concentrations tested (25-300 nM).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…1). We and others reported previously that sulprostone, a selective EP 3 -agonist, does not activate platelets on its own, but shows a potentiation of platelet aggregation induced by various agonists, such as U46619, collagen and ADP [18,[24][25][26]. We found that both EP 3 -antagonists showed a concentration-dependent inhibitory effect of the sulprostone-dependent potentiation of U46619-induced aggregation, which was significant for all concentrations tested (25-300 nM).…”
Section: Resultssupporting
confidence: 61%
“…PGE 2 was then measured by a specific enzyme immunoassay. Values are mean of duplicate determinations of one experiment influence platelet function in human blood [25]. Another difference of murine and human platelets has been observed recently by Kuriyama et al, who found a much higher inhibitory potency of a selective EP 4 -receptor-agonist in human platelets as compared to murine platelets [16].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, even at an early time-point (1 min), we could not detect any permissive effect of EP3 stimulation on thrombus formation in whole blood under flow, which is in sharp contrast to ADP-induced adhesion of washed platelets to fibrinogen, where EP3 stimulation significantly accentuated the response. Moreover, it was reported that platelet aggregation in response to collagen was indeed augmented by sulprostone in whole blood aggregometry [18,31] . Although we cannot offer a conclusive explanation for this apparent contradiction at present, it might be hypothesized that collagen fully activates platelets in whole blood, which is further accentuated under high flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These similarities suggest that murine data on atherothrombosis could be transferable to humans. However, a number of publications [9,19,[29][30][31][32] questioned this translation. In short, they showed that the effect of PGE2 on human platelets is restricted to inhibition, is dependent on the nature of the agonist, is variable amongst individuals or even is restricted to an in vitro feature.…”
Section: Does the Platelet Ep3 Paradigm Apply To Human Platelets?mentioning
confidence: 99%